Dual-Polarized Vivaldi Array Antenna for Polarimetric Through Wall Imaging Radar - Caliskan, Alper; Gunay, Oguz; Hosgor, Yasin; Turk, Ahmet Serdar; Dasbasi, Melek (IEEE, 2025)
This work proposes an adaptation of a four-element dual-polarized Vivaldi array antenna for polarimetric Through Wall Imaging Radar (TWI) applications. Leveraging the foundation of the antenna is optimized to meet the stringent requirements of polarimetric SAR systems, including wideband operation, high gain, and polarization diversity. The design incorporates advanced techniques such as edge corrugations and array configuration to achieve superior radiation performance over a wide frequency range. These modifications ensure robust polarization purity and gain stability, which are critical for accurately retrieving polarimetric information. The proposed antenna operates over a frequency range of 0.4-3 GHz, achieving 10 dBi gain and maintaining a reflection coefficient below -10 dB across the band. The dual-polarized feed networks ensure seamless horizontal and vertical polarization support, which is essential for capturing polarimetric data. The performance of this antenna for detecting symmetrical targets behind walls or longitudinal targets such as pipes has been verified by measurement.
Keywords: Vivaldi array antenna; dual polarized; ultrawide band; Computer Science; Engineering